ISLAMOPHOBIA SEBAGAI STRATEGI AMERIKA MEMPERTAHANKAN HEGEMONI DUNIA - Novitasari Ayu Setianingsih (HI 16 UMY 090, 2016)
*90 Currently, United States as a superpower has experienced over-stretched that we can see in the two wars that occurred after the 9/11. This accident rise some countries confidence against the brave United States. And it is increasingly demonstrating the existence of the United States began replaced as a superpower or the ruler of the world. And this year become a witness of how the United States busy to defend their position as a superpower. This article will explain the problems that occur within United States while defending influence of United States in the world with Islamophobia. To address the problem, the analisys of this article based on the power of United States and Analysis Framing. Keywords : United States, Islamophobia, Hegemony, Power, Framing